The Relationship Between Biometric Features of Trees and the Intensity of Birch Sap Leakage in Various Forest Sites - Szczepan Kopeć; Paweł Staniszewski; Robert Tomusiak; Maciej Bilek; Dariusz Zastocki; Tadeusz Moskalik (Applied Sciences)
The use of non-wood forest products plays a significant role in sustainable development, especially in the context of regional development. One of the most important and promising raw materials is birch sap, which in European conditions is obtained mainly from silver birch (Betula pendula Roth). Research on the utility value of birch sap and the influence of a number of factors on its efficiency and quality has been carried out in many research centers, but so far, there are not many studies on the variability of such parameters as a function of time, taking into account the entire period of sap leakage. This research was carried out in birch stands of approximately 80 years in three forest site types: mixed coniferous forest, mixed broadleaved forest, and broadleaved forest. In each site, nine sample trees were selected using Hartig’s method. The daily and all-season sap yield obtained from individual trees was statistically characterized. The relationship between birch sap yield and select quantitative (tree height, absolute and relative crown length, and slenderness) and qualitative (forest site type, tree thickness class, and sap harvesting period) variables was examined. For the first time in the literature on the subject, there is a proposal to distinguish the phases of obtaining birch sap, which may bring new knowledge, both in relation to daily productivity and the quality of the sap. As a result, the smallest amount of sap was found in the initial leak phase, a slightly higher amount was found in the final phase, and the largest amount was found in the main phase. Regarding the forest site type and the interaction between the collection phase and forest site type, no statistically significant relationship with the average amount of obtained sap was found.